Association of renin angiotensin aldosterone system inhibitors and outcomes of hospitalized patients with COVID-19 - SİLİ, ULUHAN; BİLGİN, HÜSEYİN (My University, 2022)
Copyright © 2022 by the Society of Critical Care Medicine and Wolters Kluwer Health, Inc. All Rights Reserved.OBJECTIVES: To determine the association of prior use of renin-angiotensin-aldosterone system inhibitors (RAASIs) with mortality and outcomes in hospitalized patients with COVID-19. DESIGN: Retrospective observational study. SETTING: Multicenter, international COVID-19 registry. SUBJECTS: Adult hospitalized COVID-19 patients on antihypertensive agents (AHAs) prior to admission, admitted from March 31, 2020, to March 10, 2021. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Data were compared between three groups: patients on RAASIs only, other AHAs only, and those on both medications. Multivariable logistic and linear regressions were performed after controlling for prehospitalization characteristics to estimate the effect of RAASIs on mortality and other outcomes during hospitalization. Of 26,652 patients, 7,975 patients were on AHAs prior to hospitalization. Of these, 1,542 patients (19.3%) were on RAASIs only, 3,765 patients (47.2%) were on other AHAs only, and 2,668 (33.5%) patients were on both medications. Compared with those taking other AHAs only, patients on RAASIs only were younger (mean age 63.3 vs 66.9 yr; p < 0.0001), more often male (58.2% vs 52.4%; p = 0.0001) and more often White (55.1% vs 47.2%; p < 0.0001). After adjusting for age, gender, race, location, and comorbidities, patients on combination of RAASIs and other AHAs had higher in-hospital mortality than those on RAASIs only (odds ratio [OR] = 1.28; 95% CI [1.19-1.38]; p < 0.0001) and higher mortality than those on other AHAs only (OR = 1.09; 95% CI [1.03-1.15]; p = 0.0017). Patients on RAASIs only had lower mortality than those on other AHAs only (OR = 0.87; 95% CI [0.81-0.94]; p = 0.0003). Patients on ACEIs only had higher mortality compared with those on ARBs only (OR = 1.37; 95% CI [1.20-1.56]; p < 0.0001). CONCLUSIONS: Among patients hospitalized for COVID-19 who were taking AHAs, prior use of a combination of RAASIs and other AHAs was associated with higher in-hospital mortality than the use of RAASIs alone. When compared with ARBs, ACEIs were associated with signifcantly higher mortality in hospitalized COVID-19 patients.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Yoğun Bakım; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Intensive Care; Health Sciences; Klinik Tıp (MED); Klinik Tıp; YOĞUN BAKIM; Clinical Medicine (MED); CLINICAL MEDICINE; CRITICAL CARE MEDICINE; Yoğun Bakım Tıbbı; Critical Care and Intensive Care Medicine; antihypertensive agents; COVID-19; mortality; outcome; renin-angiotensin-aldosterone system inhibitors; RECEPTOR BLOCKERS; DISEASE; COHORT